2014
DOI: 10.1186/2193-1801-3-366
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy dose reduction due to chemotherapy induced peripheral neuropathy in breast cancer patients receiving chemotherapy in the neoadjuvant or adjuvant settings: a single-center experience

Abstract: PurposeTaxanes are a cornerstone treatment in early and advanced stage breast cancer and in other common solid tumor malignancies; however, the development of chemotherapy induced peripheral neuropathy (CIPN) often necessitates dose-reduction, which may hamper the effectiveness of the drug and compromise survival outcomes especially when used in the adjuvant setting. Limited literature is available on the prevalence and severity of dose reduction due to CIPN. We sought to determine the frequency and severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
81
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 40 publications
(43 reference statements)
6
81
2
Order By: Relevance
“…These sensory changes can be debilitating to the extent that a reduction in the dose of therapy given to a patient is required. For example, a recent report found that 17% of patients receiving the chemotherapeutic agent paclitaxel required a dose reduction because of CIPN, and such dose reductions have been linked to poorer survival rates [2]. …”
mentioning
confidence: 99%
“…These sensory changes can be debilitating to the extent that a reduction in the dose of therapy given to a patient is required. For example, a recent report found that 17% of patients receiving the chemotherapeutic agent paclitaxel required a dose reduction because of CIPN, and such dose reductions have been linked to poorer survival rates [2]. …”
mentioning
confidence: 99%
“…Similarly, a prior single-institution retrospective analysis demonstrated higher risk of TIPN for AAs. 8-10 …”
Section: Discussionmentioning
confidence: 99%
“…Most cases may develop myalgias or arthralgias [2] . However, in its severe form, dose reduction is required reducing the efficacy of the drug especially in breast cancer treatment [11] .…”
Section: Chemotherapy Induced Peripheral Neuropathy (Cipn)mentioning
confidence: 99%
“…This leads to disruption of peripheral nerve signaling causing sensory, motor, or autonomic peripheral neuropathy influencing the patient routine daily activities or even causes significant disability [8][9][10][11] .…”
Section: Chemotherapy Induced Peripheral Neuropathy (Cipn)mentioning
confidence: 99%